Was Sarbanes–Oxley Costly? Evidence from Optimal Contracting on CEO Compensation - GAYLE, GEORGE‐LEVI; LI, CHEN; MILLER, ROBERT A. (Journal of Accounting Research, 2022)
ABSTRACT This paper investigates the effects of regulatory interventions on contracting relationships within firms by examining the impacts of the Sarbanes–Oxley (SOX) Act on CEO compensation. Using panel data of the S&P 1500 firms, it quantifies welfare gains from a principal–agent model with hidden information and hidden actions. It finds that SOX: (1) reduced the conflict of interest between shareholders and their CEOs, mainly by reducing shareholder loss from CEOs deviating from their goal of expected value maximization; (2) increased the cost of agency, or the risk premium CEOs are paid to align their interests with those of shareholders; (3) increased administrative costs in the primary sector (which includes utilities and energy) but the effect in the other two broadly defined sectors, services and consumer goods, was more nuanced; and (4) had no effect on the attitude of CEOs toward risk.